The Transformation of Religious Ideology in Cultural Representation in the Context of Da'wah in Palopo City - Sukirman Sukirman; Mawardi Mawardi (Bale Literasi: Lembaga Riset, Pelatihan & Edukasi, Sosial, Publikasi, 2025)
This study examines the transformation patterns used by da'is in expressing religious ideologies through the empowerment of cultural forms. The purpose of this research is to reveal the forms of culture used by the dai in Palopo City in conveying the message of da'wah. The research uses a qualitative approach, specifically ethnographic research, lasting two months, namely from June to July 2021. The da'is' research subjects were purposively selected as data sources. Data acquisition was carried out by tapping (recording) with Handycam equipment. The form of data is in the form of statements that contain the form of culture. Data were analysed using a hermeneutic approach (interpretation, interpretation) and critical discourse analysis. Based on the results of data analysis, it was found that the form of culture was used as a pattern in representing the message of da'wah which consisted of (1) the delivery of ideology through stories, (2) the delivery of ideology through roles and positions, (3) the delivery of ideology through social facts, (4) the delivery of ideology through self-efficacy, and (5) the delivery of ideology through local language. The form of cultural aspects becomes an instrument to transform the message of da'wah.